Barnardo Boys - Elliott, Robin (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
AbstractThe opera Barnardo Boys, with music by Clifford Crawley and libretto by David Helwig, was premiered in Kingston, Ontario in May 1982. Inspired by the example of Benjamin Britten, the creators of the opera regarded community involvement and cooperation between amateurs and professionals as essential to the production of the work. There was only one imported professional singer in the cast—Jan Rubes, who was hired to play the lead role of Albert Ashby. Both the libretto and the music of the opera make use of a combination of pre-existing and newly created source materials. This approach is seen to be typical of a Canadian preference for the genre of documentary opera, which parallels an engagement with historical fiction on the part of Canadian novelists.